2018
DOI: 10.1051/matecconf/201824001029
|View full text |Cite
|
Sign up to set email alerts
|

Leidenfrost evaporation of water droplet

Abstract: The present paper examines the behaviour of a single large droplet levitating over a hot surface, unsteady mass of the droplet, and heat transfer. It was assumed that the evaporation from the upper surface of the droplet is negligibly small compared with the amount discharged from its lower surface, and the heat transfer coefficient is the power function of droplet orthogonal projection onto the heating surface. Based on the photographic documentation, the dependence of the droplet projection on time was appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In the paper conclusions, the authors postulated linear dependence between droplet lifetime and its initial volume and inversely proportional relation between droplet lifetime and temperature. In the study [24], it was shown that in order to apply this dependence for different parameters, is it necessary to choose the base of power on case-by-case basis. That additionally makes it difficult to apply the formula for general use.…”
Section: Heat Transfer Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the paper conclusions, the authors postulated linear dependence between droplet lifetime and its initial volume and inversely proportional relation between droplet lifetime and temperature. In the study [24], it was shown that in order to apply this dependence for different parameters, is it necessary to choose the base of power on case-by-case basis. That additionally makes it difficult to apply the formula for general use.…”
Section: Heat Transfer Analysismentioning
confidence: 99%
“…The droplet projection formula does not depend on the initial droplet mass, which was confirmed by reported measurements. The proposed dependence was used by Orzechowski [24], who worked out a formula, expressed as infinite series, for droplet mass change over time. The effective application of the formula, however, makes it necessary to individually select coefficients that describe the area of the droplet projection.…”
Section: Introductionmentioning
confidence: 99%